Flood Mitigation Strategies: Integrating Hydrologic Engineering Systems- River Analysis Systems for Effective Management of Paremang Watershed - Mirzaq, Muhammad Rozali; Rijal, Syamsu; Soma, Andang Suryana; Chairil, A (Jurnal Sylva Lestari, 2024)
The Hydrologic Engineering System-River Analysis System (HEC-RAS) model is a model that can display water surface cross-sections in both 1D and 2D forms. That way, HEC-RAS can predict the amount of peak discharge that results in flooding. This study aims to see the distribution of flood areas in the Paremang Watershed as a basic form of mitigation activity for flood events. A flood disaster analysis was conducted using the HEC-RAS model. The HEC-RAS model data includes river water discharge data from the Soil and Water Assessment Tools (SWAT) analysis, which is an overlay of topography, land cover/use, soil characteristics and climate data from authorized agencies, and direct field observations. The results showed that the flood area was 2,722.38 ha, affected by high rainfall conditions, steep slopes accelerating water flow, and land cover dominated by rice fields, bushes and dry land agriculture. The condition increases surface flow, stimulating the amount of water discharged. This resulted in flooding in most of the downstream and middle areas of the Paremang Watershed in Luwu Regency. Therefore, mitigation in the form of land use planning is needed. The plan is led by the Ministry of Agrarian Affairs and Spatial Planning, which includes other sectors ranging from forestry, agriculture, fisheries, tourism, and public works. This could support in developing policies ranging from forest rehabilitation, social forestry, community forests, expansion of agroforestry patterns, ecotourism development, and flood mitigation such as technical buildings. Keywords: flood areas distribution, HEC-RAS model, Paremang, soil and water assessment tools, watershed